1985
DOI: 10.1113/jphysiol.1985.sp015911
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of inward and outward potassium currents in the macrophage‐like cell line J774.1.

Abstract: 5. The outward current was time-and voltage-dependent. The instantaneous I/ V curves derived from tail experiments reversed at the potassium equilibrium potential (EK). A tenfold change of [K]0 shifted the reversal potential 52 mV, indicating that the current was carried by potassium. This conductance activated at potentials positive to -50 mV, plateaued at potentials positive to -10 mV and inactivated completely with an exponential time course at all potentials. At voltages positive to -25 mV the rate of inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
100
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 36 publications
14
100
0
Order By: Relevance
“…Thus the resting potential of many animal cells is close to E K+ . Most data suggest a Vm for the macrophage close to E K+ that varies with changes in [K + ] o (Gallin & Sheehy, 1985;Judge et al, 1994 (Gallin & Sheehy, 1985), but suggesting the contribution of other ions. A contribution of the electrogenic activity of a Na + /K + ATPase pump (Gallin & Livengood, 1983) of about 6 mV to the macrophage Vm could explain the deviation found.…”
Section: Macrophage Passive Membrane Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus the resting potential of many animal cells is close to E K+ . Most data suggest a Vm for the macrophage close to E K+ that varies with changes in [K + ] o (Gallin & Sheehy, 1985;Judge et al, 1994 (Gallin & Sheehy, 1985), but suggesting the contribution of other ions. A contribution of the electrogenic activity of a Na + /K + ATPase pump (Gallin & Livengood, 1983) of about 6 mV to the macrophage Vm could explain the deviation found.…”
Section: Macrophage Passive Membrane Propertiesmentioning
confidence: 99%
“…Values of around -75 mV have been recorded (McCann et al, 1987;Gallin & Sheehy, 1985;Buisman et al, 1988), and it has been suggested that time of adherence is not important because rapid hyperpolarization was observed after only 30 minutes post-adhesion (Gallin & Sheehy, 1985). Values of -60 to -70 mV were recorded in J774 and in peritoneal macrophages (Randriamampita & Trautmann, 1987).…”
Section: Macrophage Passive Membrane Propertiesmentioning
confidence: 99%
See 3 more Smart Citations